การศึกษาการดำเนินการนิเทศการสอนของกระบวนการศึกษาผ่านบทเรียน (Lesson Study) โรงเรียนราชินีบน A STUDY OF INSTRUCTIONAL SUPERVISORY OPERATIONS THROUGH LESSON STUDY PROCESS AT RAJINIBON SCHOOL - วงศาเอียด, จิราภรณ์; สุดรุ่ง, จุไรรัตน์ (An Online Journal of Education, 2017)
การวิจัยในครั้งนี้ มีวัตถุประสงค์ (1) เพื่อศึกษาการดำเนินการนิเทศการสอนของกระบวนการศึกษาผ่านบทเรียน (Lesson Study) (2) เพื่อศึกษาปัญหาการดำเนินการนิเทศการสอนของกระบวนการศึกษาผ่านบทเรียน (Lesson Study) ระดับประถมศึกษา โรงเรียนราชินีบน ประชากรในการวิจัยในครั้งนี้คือผู้บริหาร และครูผู้สอนโรงเรียนราชินีบน จำนวน 75 คน เครื่องมือในการวิจัยเป็นแบบสอบถาม 1 ฉบับ วิเคราะห์ข้อมูลโดยใช้สถิติวิเคราะห์ข้อมูลโดยการแจกแจงความถี่ หาค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1) ด้านการเตรียมการดำเนินการนิเทศ พบว่า การเตรียมการดำเนินการนิเทศมีการปฏิบัติอยู่ในระดับมาก โดยการจับกลุ่มการพัฒนาบทเรียนร่วมกันมีค่าเฉลี่ยของการปฏิบัติสูงกว่าข้ออื่นๆ ปัญหาที่พบคือการอบรมระยะสั้นทำให้ครูขาดความรู้ความเข้าใจขั้นตอนการนิเทศการสอนของกระบวนการศึกษาผ่านบทเรียน 2) ด้านการดำเนินการนิเทศ พบว่า มีการปฏิบัติอยู่ในระดับมาก โดยสมาชิกในกลุ่มนำแผนการจัดการเรียนรู้ที่สร้างขึ้นไปดำเนินการสอนในชั้นเรียนมีค่าเฉลี่ยการปฏิบัติสูงกว่าข้ออื่นๆ ปัญหาที่พบคือ การนิเทศการสอนไม่เป็นไปตามแผน การจัดการเรียนรู้ 3) ด้านการติดตามประเมินผลการนิเทศ พบว่า การปฏิบัติอยู่ในระดับปานกลาง โดยการเก็บข้อมูลสรุปผลการประเมินอย่างเป็นระบบมีค่าเฉลี่ยการปฏิบัติสูงกว่าข้ออื่นๆ ปัญหาที่พบคือ ผู้บริหารและครูมีเวลาไม่ตรงกัน ทำให้การติดตามประเมินผลขาดความต่อเนื่อง The objective of this research were (1) to study of the instructional supervisory operations through the lesson study process and (2) to study Pproblems of instructional supervision operations through the lesson study process at Rajinibon school. The population that we studiedy in the research are included 75 administrators and tTeachers. A at Rajinibon school all together 75 persons. The instrument used that we use in this research is was a set of questionnaires. Statistics methods are used in data analysis by included using frequency, percentage, average, and Standard Ddeviation. The research findings were as follows:. 1) The preparation operations supervision. There is much preparation of supervision, especially to join in groups to improve lesson study. The problems in supervision preparation is short term trading , which causes a lack of understanding. I in the supervision of preparation of instructional supervisory operations through lesson study process. 2)In terms of Tthe instructional supervisory operations,. I it has been found that the implementation of supervision is in at a high level, especially using preponed learning plans in the class by group members. Problems included that is I instructional Ssupervision does not follow the lesson plans. 3) The monitoring and evaluation. It has been found that the iImplementation of monitoring and evaluation is at ian intermediate level, which means that systematic data collection and evaluation are well well-implemented. Problems found were that is A administrators and teachers have not made the corresponding evaluations, lacking continuity.